Prime Time for G-Protein-Coupled Receptor Heteromers as Therapeutic Targets for CNS disorders: The Dopamine D1-D3 Receptor Heteromer - Ferre, Sergi; Lluis, Carmen; Luis Lanciego, Jose; Franco, Rafael (CNS & Neurological Disorders - Drug Targets, 2010)
A number of G-protein-coupled receptors (GPCRs) are currently under consideration as potential therapeutic targets for drugs acting in the central nervous system (CNS). Attempts to discover new medications have operated under the assumption that GPCRs are monomers and that a specific drug activates one single receptor coupled to one single signal transduction mechanism. In the neuronal membrane, GPCRs are now known to be arranged into homo- and hetero-oligomers; drugs acting on a single receptor within a specific heteromer context are thought to induce a particular downstream signaling. However, there is recent evidence showing that heteromertailored drugs can be designed that display different affinities for a given receptor depending on the receptor partners contained within the heteromer. It can therefore be predicted that customized drugs targeting a specific receptor heteromer in the CNS might imporove safety and efficacy for their therapeutic targets. Finally, it will be important to identify receptor heteromers that are involved in the pathogenesis of diseases, such as the recently discovered dopamine D1-D3 receptor heteromer, which might play a key role in L-DOPA-induced dyskinesia in Parkinson's disease.
Keywords: heteromer-tailored drugs